1982
DOI: 10.1111/j.1469-8137.1982.tb03286.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF A FOREIGN POLLEN ON OVULE DEVELOPMENT IN DIERVILLA LONICERA (CAPRIFOLIACEAE)

Abstract: Summary When pollen from Hieracium floribundum Wimmer and Grab. (Compositae) was applied to stigmas of Diervilla lonicera Mill. (Caprifoliaceae) in mixtures with Diervilla pollen, Diervilla fecundity was strongly depressed. While this phenomenon is unlikely to be of importance to Diervilla under field conditions, this property of Hieracium pollen may have stronger effects on other ecological associates. The only other reported instance of inhibitory pollen is from Parthenium hysterophorus L., which, like Hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 20 publications
1
99
1
Order By: Relevance
“…For example, Sukhada and Jayachandra (1980) found that pollen germination and pollen tube growth of conspecific pollen on eight test species was inhibited to varying degrees by the application of pollen from the tropical weed Parthenium hysterophorus (Asteraceae), with germination in one of those, Crotalaria pellida (Leguminosae), being completely suppressed. A similar allelopathic effect of foreign pollen was suggested in the study of Thomson et al (1981) where the addition of Hieracium floribundum (Asteraceae) pollen significantly reduced embryo development in DiervilIa lonicera (Caprifoliaceae), while Randall and Hilu (1990) showed that reduction in fruit set in Impatiens capensis (Balsaminaceae) pollinated with mixtures of conspecific pollen and pollen from the related I. pallida was due to clogging of the stigma and style with foreign pollen tubes which interfered with the conspecific ~ fertilisation process. It was very unusual to observe germination of foreign pollen on orchid stigmas and therefore interspecific pollen tube competition is unlikely to be an explanation of fertilisation failure.…”
Section: Effects Of Heterospecific-pollen Deposition On Reproductive mentioning
confidence: 78%
“…For example, Sukhada and Jayachandra (1980) found that pollen germination and pollen tube growth of conspecific pollen on eight test species was inhibited to varying degrees by the application of pollen from the tropical weed Parthenium hysterophorus (Asteraceae), with germination in one of those, Crotalaria pellida (Leguminosae), being completely suppressed. A similar allelopathic effect of foreign pollen was suggested in the study of Thomson et al (1981) where the addition of Hieracium floribundum (Asteraceae) pollen significantly reduced embryo development in DiervilIa lonicera (Caprifoliaceae), while Randall and Hilu (1990) showed that reduction in fruit set in Impatiens capensis (Balsaminaceae) pollinated with mixtures of conspecific pollen and pollen from the related I. pallida was due to clogging of the stigma and style with foreign pollen tubes which interfered with the conspecific ~ fertilisation process. It was very unusual to observe germination of foreign pollen on orchid stigmas and therefore interspecific pollen tube competition is unlikely to be an explanation of fertilisation failure.…”
Section: Effects Of Heterospecific-pollen Deposition On Reproductive mentioning
confidence: 78%
“…It is unlikely that the reduction is due to pollen allelopathy given that previous studies of allelopathy show a considerable reduction in seed set with only a small number of allelopathic pollen grains present. For example, Thomson et al (1981) found almost complete reproductive failure in ovule development with additions of 50% allelopathic pollen. Murphy and Aarssen (1995d) found a 70% reduction in seed set when pollen extract from only five pollen grains from Phleum pratense was applied to stigmas of Agropyron repens.…”
Section: Foreign Pollenmentioning
confidence: 98%
“…Such interspecific pollen transfer (IPT; Waser 1983, also Rathcke 1983) has been recognized as an important mechanism through which plants can compete for pollination services (Waser 1983;Rathcke 1983), in part because it can impair seed set even in the absence of pollinator limitation (Waser 1983;Randall and Hilu 1990;Petanidou et al 1995;Bergman 1996). IPT can reduce seed production in several ways, including pollen allelopathy (Char 1977;Sukhada and Jayachandra 1980;Thomson et al 1981;Murphy and Aarssen 1995a, b, c, d), stigma clogging (Shore and Barrett 1984;Galen and Gregory 1989;Proctor et al 1996), stigma closing (Waser and Fugate 1986), stylar clogging (Palmer et al 1989;Scribailo and Barrett 1994), and stylar inhibition (Williams et al 1982;Cruzan 1990Cruzan , 1993. Even when IPT does not reduce seed set (Schemske 1981;Shore and Barrett 1984;Kohn and Waser 1985;Kwak and Jennersten 1986;Galen and Gregory 1989;McGuire and Armbruster 1991), it may reduce male fitness (Waser 1978;Campbell and Motten 1985;Feinsinger et al 1986;Jennersten and Kwak 1991; McGuire and Armbruster 1991) through pollen loss.…”
Section: Introductionmentioning
confidence: 95%
“…A link may also exist between the number of heterospecific grains received by the plants we examined and floral fecundity or plant fitness (Waser 1978b, Thomson et al 1981, Rathcke 1983. Numbers ofheterospecific grains varied widely within and among the four species.…”
Section: Ls Variation Among Pollen Loads Significant To the Plants Inmentioning
confidence: 99%